Péptidos inmunogénicos del gluten en deposiciones. Nuevo método para evaluar la adherencia a la dieta en pacientes celíacos - Miranda B., Julio; Covarrubias R., Natalia; Araneda M., Gonzalo; Hurtado H., Carmen; Defilippi G., Claudia (Revista Hospital Clínico Universidad de Chile, 2016)
Celiac disease (CD) is an autoimmune pathology caused by the ingestion of gluten in geneticallysusceptible people, currently considered multisystemic. The treatment of CD is a lifelong strictGluten-Free Diet (GFD), which allows a symptomatic improvement in most patients and achieveintestinal mucosa healing confirmed with histological study. The adherence to the GFD isvariable, arguing as possible factors related to failure the economic, cultural, social aspectsand the consumption of gluten inadvertently. The management of celiac patients contemplatesinstructing in the proper follow-up of GFD and evaluating their adherence. So far, the only wayto assess adherence to GFD is through surveys, self-reports of eating habits and serology,being the main disadvantage the subjectivity factor. Recently the immunogenic gluten peptideshave acquired relevance for the objective evaluation of the adherence to the GFD and themeasurement appears as an efficient and sensitive option to determine the gluten intake,providing relevant information for the clinical management.